Structure, magnetic and microwave properties of FeNi invar nanoparticles obtained by electrical explosion of wire in different preparation conditions. (November 2016) - Kurlyandskaya, G.V.; Bhagat, S.M.; Bagazeev, A.V.; Medvedev, A.I.; Ballesteros, A.; Beketov, I.V.; Safronov, A.P.
Abstract: Magnetic nanoparticles (MNPs) of close to invar (Fe0.635 Ni0.365 ) composition were prepared by the electrical explosion of wire using different conditions to insure different values of overheating rates. X-ray diffraction, transmission electron microscopy, low temperature nitrogen adsorption, magnetic and microwave measurements were used for the characterization of MNPs. Increase of the energy injected into the wire led to increase of the specific surface ( S sp ) of the produced MNPs from 4.6 to 13.5 m 2 /g. The fabricated MNPs were spherical and weakly aggregated with the average weighted diameter in the range of 54–160 nm depending on the S sp . The phase composition of FeNi MNPs consists of two solid solutions of Ni in α-phase and γ-phase lattices. The increase of the energy injected into the wire leads to increase of the α-phase from 5 to 10 wt% as the injected energy raised from 0.8 to 2.5 times the sublimation energies of the wire material. Comparative analysis of structure magnetic and microwave properties showed that the obtained MNPs are important magnetic materials with high saturation magnetization and significant zero field microwave absorption which can be expected to lead to important technological applications. Highlights: Nanoparticles of close to invar composition were prepared by the electrical explosion of wire. Different conditions insured different values of overheating rates. Increase of the energy injected into the wire led to increase of the specific surface value. MNPs were spherical with the average weighted diameter in the range of 54–160 nm. MNPs are materials with high saturation magnetization and significant zero field microwave absorption.